DESIGN OF RESEARCH-BASED LEARNING MODEL AT UNIVERSITAS TIDAR - Sukarno Sukarno; Sri Haryati; Sri Sarwanti (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
This study aims to generate a product of research-based learning model design at Universitas Tidar. The 21st century era, the learning process should be able to develop all the skills needed by students to be able to live in the 21st century. Therefore, it is necessary to develop a learning model design that is in accordance with the 21st century development, one of which is the research-based learning model. This study applied Research and Development (R&D) method, but limited to the expert validation stage. Instruments of test used were questionnaires to determine the feasibility and expert judgments related to the product being developed. The result indicates that valid and feasible stages of research-based learning activities have been composed to be implemented at Universitas Tidar based on the results of the expert judgments. The stages of learning activities include identifying the problem, framing the question, proposing hypothesis, investigating, analyzing the data, evaluating hypothesis, and communicating the result.